A transparent-to-gray electrochromic device based on an asymmetric viologen. (12th November 2020) - Ling, Huan; Dai, Hongbo; Su, Fengyu; Tian, Yanqing; Liu, Yan Jun
Abstract : A transparent-to-gray electrochromic device (ECD) based on an asymmetric viologen was fabricated and characterized. Abstract : A transparent-to-gray electrochromic device (ECD) based on an asymmetric viologen was fabricated and characterized. The core material derived from novel bipyridine salt (named 1-(2-(diethoxy-phosphoryl)ethyl)-1′-(4-vinylbenzyl)-[4, 4′-bipyridine]-1, 1′-diium chloride bromide, DVB) combined with complementary species of ferrocene was assembled in a device with a simple configuration of ITO/EC solution/ITO. The device was first converted to blue color from transparent when 1.0 V was applied, and then neutral gray color when the potential bias was increased to 2.0 V. Meanwhile, the corresponding optical contrasts (Δ T ) were 54.5% and 22% at 392 nm and 605 nm, respectively. In addition, a good coloration efficiency of 128.9 cm 2 C −1 at 2.0 V and fast switching time (<2.5 s) were obtained. Finally, satisfied stability with 43.8% of Δ T (maintaining 80% of initial Δ T at 392 nm) was achieved after 2000 cyclic processes, which paves a new way to design colorless to neutral color ECDs.